2020
DOI: 10.1210/clinem/dgz114
|View full text |Cite
|
Sign up to set email alerts
|

Maternal B12, Folate and Homocysteine Concentrations and Offspring Cortisol and Cardiovascular Responses to Stress

Abstract: Context Imbalances in maternal 1-carbon nutrients (vitamin B12, folate) have been shown to be associated with higher offspring cardiometabolic risk markers in India. Objective We examined the hypothesis that low plasma vitamin B12 (B12) and high folate and homocysteine concentrations in the mother are associated with higher hypothalamic–pituitary–adrenal axis (cortisol) and cardiovascular responses during the Trier Social Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…One study (53) reported bone mineral density in offspring. Four studies (19,(54)(55)(56) reported maternal and birth characteristics in relation to offspring metabolic and cardiovascular outcomes and all of them were performed on ongoing longitudinal prospective birth cohorts (Supplementary Table 6).…”
Section: Metabolic and Cardiovascular Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…One study (53) reported bone mineral density in offspring. Four studies (19,(54)(55)(56) reported maternal and birth characteristics in relation to offspring metabolic and cardiovascular outcomes and all of them were performed on ongoing longitudinal prospective birth cohorts (Supplementary Table 6).…”
Section: Metabolic and Cardiovascular Functioningmentioning
confidence: 99%
“…Another study (55) from the Mysore cohort examined cortisol and cardiovascular responses to a stress test in adolescents (at 13.5yrs) and found that vitamin B12 deficiency in mothers and a higher homocysteine was associated with a greater cortisol response (B=0.36 95%CI 0.16, 0.57) and greater heart rate response (B=0.13, p=0.01) respectively. A study (56) in offspring aged 3 to 8 years, examined cardiac autonomic nerve activity as measured by heart rate variability (HRV) in relation to maternal vitamin B12 status.…”
Section: Observational Studiesmentioning
confidence: 99%